ANALISIS KEUNTUNGAN USAHA PENGOLAHAN MINYAK NILAM DI NAGARI RABI JONGGOR KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT SUMATERA BARAT - Fibrasia, Fibrasia; Sriyoto, Sriyoto; Arianti, Nyayu Neti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
One of the purposes of a farmer doing the business is to get profit. This research aimed to determine the profit of the patchouli oil processing in Nagari Rabi Jonggor and to analyze the factors that affect the profit. The data of the study were taken from 39 respondents. All population of patcahouli oil processors were got to be respondents. The formula used to analyze the profit gain was ? = TR-TC, whereas to determine the factors that affected the profit using the multiple linear regression with F-test and t-test at the confidence level of 95% (? = 0.05). The results showed that the average processing profit of patchouli oil were Rp. 439,815.00 for each refinery and the factors affected negatively to the processing profit of patchouli oil were all input price variables like the price of raw materials, kerosene, firewood, and labor. The price of patchouli oil itself did not significantly affect.